Por uma estética filosófica sobre os (des) concertos da música: contribuições para a formação profissional técnica de nível médio em música - Ribeiro, Alan Barcelos (2016)
In this work, the research problem was how to incorporate aesthetic elements from Philosophy of modern music by Theodor W. Adorno in the students training of higher secondary technical-professional education in musical instrument offered by state conservatories of Minas Gerais. As overall objective was to understand how are sedimented the aesthetic philosophical reflections on the curriculum of these courses. The specific objectives were directed in order to identify the presence or absence of aesthetic reflections on technical-professional education in music and present aesthetic values that contribute of critical, reflective and sensitized individuals‟ formation. The research is qualitative with data analysis of interpretative basis. As investigative procedures were adopted literature review, bibliographical and documentary analysis from which it was found the hypothesis of there is a possible lack of aesthetic content in higher secondary technical-professional education in music. Reflecting on the theme proposed in philosophical perspective comprises a training guided in the art, with a view to awaken for sensitivity and cognitive development built from the critical character, reflective, autonomous and thus, emancipating. Therefore, it was used the concepts of Training, Emancipation, Fetishes, Regression, Cultural Industry and New music that underpinned understanding of the aesthetic proposal undertaken by Adorno in his work „Philosophy of modern music‟. By means reflections made, it was possible to observe that the so-called Modern Music presents a new way to explore the musical elements designing an aesthetic uniqueness essential for musician formation, owing to presence of sensitive apparatus, cognitive, historical, social and critical involving music forefront. As result, in this research was considered imperative urge for aesthetic issues in the curriculum of the current disciplines or claim for a new discipline specifically to handle the philosophical aesthetic context of higher secondary technical-professional education in music.